ASSESSING THE POTENTIAL OF NUDGE AS A TOOL FOR PUBLIC POLICY - Eka Novian Gunawan (Lembaga Riset dan Pengkajian Strategi Pemerintahan IPDN, 2022)
o solve societal problems, governments should open any means alternative tools of public policy. One of the public policy tools is nudge. Nudge relies on behavioral science to improve people’s decisions through small changes in the environments within which people make choices. However, there is criticism about using nudges in public. This paper will try to picture the discussion and debates on the nudge. The literature study is conducted to describe and understand a condition and seek views on a focused topic. The paper shows how the nudge operates and which system works better. In addition, it shows the debates on nudges about transparency and legitimacy